الكفاءة الاقتصادية لانتاج محصول الرز في إقليم كوردستان العراق - مساعد, محمد رؤوف سعيد استاذ; مساعد, ارسلان منوچر سان احمد مدرس; مساعد, پروین محمد حمە خان مدرس (Sulaimani Journal for Humanities, 2001)
Beside food and Industrial importance of Rice crop. There is shortcome in Self-sufficiency of this crop in Iraq and ratio of cultivated Irrigation Lands by this crop is only about %7.75 of total Irrigation Lands in Kurdistan Region. The Study shows that about %47.37 of Rice cultivated place fall to Sulaimaniya Governorate, since Dohuk Governorate come at first order in amount of Rice cultivated area and Production, Sulaimaniya attains minimum level of average cost for one Ton of Production by about (I.D. 2180), average Price in Region was about (ID. 4426), Productivity was about (547 kg/Dunm) in Region where Duhok was first by about (585 kg/Dunm), and shows that Cubic form was best model to representing long run cost function for rice based upon Economic theory ,Statistical and Econometrics criteria ,optimum size of production and area to attain Economic Efficiency was (3445.8 Ton )and (2922 Dunm)respectively ,about 84.2% of cultivated place (Rice) was working inside Economies of Scale Region and Amedi has come at first by attaining about 75.3% of Economies of Scale .